Technisierung der Pflege 4. Goldegger Dialogforum Mensch und Endlichkeit - Stronegger, Willibald J.; Platzer, Johann (Bioethik in Wissenschaft und Gesellschaft, 2022)
The technologies of 'digital health' will fundamentally transform the building of relationships in healthcare and the social relationships of ageing people. This volume is devoted to three ethical and legal areas of tension. In the area of tension between personal dignity and digital care, it is a question of balancing individual ideas about a good life with those of digitised technologies. In this way, new information technologies enable both more self-determination and more complete control over everyday life. Analogously, in the area of tension between freedom and security, technology can reinforce one aspect at the expense of the other. Finally, the area of tension between simulation and authenticity revolves around the human consequences of the construction of reality. With contributions by Stefan Dinges; Michael Früh; Alina Gasser; FH-Prof.in Mag.a Dr.in Elisabeth Haslinger-Baumann; Kathrin Janowski, MSc; Dominik Kaiser, BSc; Univ.-Prof. Dr. Reinhard Klaushofer; Prof. Dr. Arne Manzeschke; Prof. Dr. Claudia Paganini; Mag Dr. Johann Platzer; Prof. Eveline Prochaska, BSc, MSc; Dr. Karin Reinmüller; Univ.-Prof. Dr. Martina Schmidhuber; Manuela Straub and Univ.-Prof. Dr. Willibald Stronegger.